ANALISIS KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN PINGGIR - Martina Gloria Sitorus; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Subdistrict of Pinggir is a government agency that has the main task to organizing public services. Public service as something that associated with fulfillment of expectations /needs of the public, which is quality service is can provide products dan services in accordance with needs and expectations of public. In fact there are still complaints from the public which is there are still people whowait because service schedule is not on time, facilities is inadequate. As for the purpose of this research is to find out about quality of public service in Subdistrict of Pinggir. Concept of theory that researcher uses is service quality according To Ratminto’s theory, there are indicators affect the quality of service which is completion time of service, cost of service, procedure of service, and facilities. This research is using qualitative research method and evaluating data with descriptive method, collecting data with interview technique, observation, and documentation from research informants. The result of this research showing that Subdistrict of Pinggir in doing public service is still not optimal yet that can be discovered by the time of sevice is uncertain, the cost of servie that are not clear, the presence of Camat less than optimal, and facilities is inadequate. Factors that influence subdistrict of Pinggir in doing public service influenced by employee discipline, untrasparent cost of service, and inadequate the facilities. Key Words : Service Quality, Public Service